PO16 Chemical composition of the essential oils of Eugenia procera (Sw) (White Myrtle) and its evaluation against Aedes aegypti larvae. - herrera romero, carolina; Romero Losada, Johan David; Sanchez Ramirez, Nina María; Castañeda Gómez, Jhon Freddy (Revista Productos Naturales, 2025)
Dengue, transmitted by the Aedes aegypti mosquito, is a serious public health problem. Current strategies, including synthetic insecticides, have failed due to mosquito resistance. In this context, essential oils from plants such as Eugenia procera are considered a promising, environmentally friendly alternative for controlling Aedes aegypti larvae. The research analyzed the chemical composition of these oils and their larvicidal effectiveness. The results showed that 100% larval mortality was achieved within 9 hours at 50 ppm, highlighting their potential for biological control.
Keywords: Aedes aegypti; Eugenia procera; Essential oils; Larvicidal activity